(untitled) (African Journal of Science, Technology and Social Sciences, 2022)
Public participation is extensively acknowledged as predominantly indispensable to the success of sanitation and water projects in rural areas in developing countries. Women are the foremost users of water schemes in rural areas and have numerous ideas on how water and sanitation management can be enhanced. Women’s participation in sanitation in South Imenti has recently surfaced as an area of interest in the past decade, there has been rapidly growing evidence of women lagging behind in taking part in sanitation. In this context, the study involved examining how management and knowledge of sanitation are gendered, determining women’s participation in sanitation development, governance and management, and evaluating the challenges hindering their participation. Qualitative and quantitative research methods were used. In-depth interviews and questionnaires were used to conduct the study. Purposive sampling was used to select three locations in South Imenti sub-county and a sample size of 100 determined using Yamane’s formula. Data was collected from December 2021 to March 2022. 75 respondents aged 18 years and above took part in the study. 58.6% (44) respondents filled the questionnaires and 41.3% (31) respondents were interviewed. The data was entered into statistical package for Social Sciences (SPSS) version 22 software and presented using descriptive statistics. The results showed that 80.4% (n=41) of the women in South Imenti were not fully taking part in sanitation projects, despite them being known as primary sanitation attendants at the household level. Women’s contribution was very minimal in sanitation activities involving community members, besides, their contribution was greatly under looked. The study findings revealed various roles played by both men and women in the sanitation group. 20.8% (n=5) of men were in charge of decision making, chairing and directing meeting discussions, and mobilization of funds for sanitation projects. 16.7%(n=4) of men provided labour during the construction of a projects, 37.5%(n=9) coordinated day to day running of projects and 25%(n=6) organized for donors’ visits as well contributed funds to the group and were key actors during elections. On another hand 80.4%(n=41) of women were involved in domestics chores like cooking for constructors, ensuring cleaningness of sanitation facilities and compounds as well 29.4% (n=15) of women welcomed and entertained guests during a meetings and led in prayers during meetings times.35.3%(n=18) of women were not included in policy and decision-making about sanitation projects since it was given a blind eye concealed under community beliefs, practices, and norms.The finding als revealed numerous determinants to women participation among them were financial rewards 27%(n=14),source of income 20%(n=10),influenced by leaders 14%(n=7) and fear of consequences 10%(n=5) .Various challenges hindered women participation where 49%(n=25)had tight schedules ,age disparity 15.7% (n=8),low literacy level 31.4%(n=16)and lack of registration fees 29.4%(n=15) among others. Women’s rights and freedoms in leadership and management abilities were hindered by old-fashioned cultural practices and busy schedules. Both men and women should be included in community sanitation projects to boost the sanitation sector in the attainment of its goals and specifically meet sanitation targets. This research study gives detailed rich information on women in sanitation, contributes to critical literature, and provides many insights for further research on women’s participation in sanitation. It also gives a greater understanding of women’s position in sanitation and reduces any kind of potential gender discrimination and promote policy implementation.